FinHealth Armenia : Reforming Public Financial Management to Improve Health Service Delivery - Chukwuma, Adanna (World Bank, Washington, DC, 2020)
This report aims to assess public financial management (PFM) bottlenecks in health service delivery and identify recommendations for the Ministry of Health (MOH) and its partners in Armenia. This PFM assessment identifies health sector–specific bottlenecks and recommends actions that the MOH and regional (Marz) health authorities can take. Governments have a central role to play in moving countries toward universal health coverage. In low- and middle-income countries, making progress toward universal health coverage involves financing mechanisms that allow for coverage for the formal sector, the poor and the informal sector, to improve the coverage of quality health services. PFM systems, the way public budgets are formed, executed, and monitored interact with health system functions to influence service delivery outcomes. This study builds on a body of research that links improved service delivery outcomes in the health sector to systems for fiscal sustainability, operational efficiency, fiscal transparency, and accountability. The evidence supports the proposition that governance matters for the effective use of public resources in health service delivery.